2016
DOI: 10.1016/j.ijscr.2016.07.054
|View full text |Cite
|
Sign up to set email alerts
|

Primary hydatid cyst of pancreas: Case report and review of literature

Abstract: HighlightsPancreatic hydatid cysts are very rare entities with an incidence ranging from 0.14% to 2%.They can masquerade as pseudocyst or cystic neoplasm of pancreas.Ultrasonography, Computed tomography and Hydatid serology help in diagnosis.Pericystectomy, Partial cystectomy with omentopexy/external drainage, Marsupialization, Cysto-enterostomy are some of the surgical options.Prophylactic preoperative and postoperative anti-helminthics(Albendazole) are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
71
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(84 citation statements)
references
References 14 publications
0
71
0
13
Order By: Relevance
“…The presenting clinical features depend on the location of the cysts within the pancreas and the size of the lesions. Although pancreatic head hydatid cysts can present with obstructive jaundice, as reported by Yattoo et al and Ahmed et al the current study's case was asymptomatic and only a dull abdominal pain was reported (1,7). The clinical features presented depend on the location and the size of the lesions.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…The presenting clinical features depend on the location of the cysts within the pancreas and the size of the lesions. Although pancreatic head hydatid cysts can present with obstructive jaundice, as reported by Yattoo et al and Ahmed et al the current study's case was asymptomatic and only a dull abdominal pain was reported (1,7). The clinical features presented depend on the location and the size of the lesions.…”
Section: Discussionmentioning
confidence: 47%
“…The clinical features presented depend on the location and the size of the lesions. The methods widely used for the diagnosis of cystic visceral lesions include serological testing, histopathology, ultrasonography (USG), computed tomography, and magnetic resonance imaging (MRI) (1,8). In spite of the high sensitivity of abdominal USG for diagnosing hydatid cysts, this method has a lower sensitivity in the case of PHC due to the retroperitoneal location and bowel gas space (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydatid disease is endemic in most parts of Iran and is hyper endemic in some areas [1][2][3]. Hydatidosis is responsible for approximately 1% of admissions to surgical wards in Iran [1,4,5].…”
Section: Introductionmentioning
confidence: 99%